2013
DOI: 10.3758/s13423-013-0392-5
|View full text |Cite
|
Sign up to set email alerts
|

Both young and older adults discount suggestions from older adults on a social memory test

Abstract: In the present study, we examined the impacts of participant age and confederate age on social memory processes. During a collaborative recall phase, young and older adult participants were exposed to the erroneous memory reports of a young or an older adult confederate. On a subsequent individual recall test, young and older adult participants were equally likely to incorporate the confederates' erroneous suggestions into their memory reports, suggesting that participant age had a minimal effect on social mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 40 publications
4
32
1
Order By: Relevance
“…For instance, source credibility plays a role. Findings show that individuals are less likely to incorporate misinformation from an older adult (Davis & Meade, ; Kwong See, Hoffman, & Wood, ), a child (Skagerberg & Wright, ), or an out‐group member (Andrews & Rapp, ), presumably because of perceived low credibility. In contrast, participants rely on information more from partners with whom they have a prior relationship (e.g., friends or romantic partners) than from strangers (French, Garry, & Mori, ; Hope, Ost, Gabbert, Healey, & Lenton, ), presumably because of perceived reliability.…”
Section: Social Transmission Of False Memories In Small Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, source credibility plays a role. Findings show that individuals are less likely to incorporate misinformation from an older adult (Davis & Meade, ; Kwong See, Hoffman, & Wood, ), a child (Skagerberg & Wright, ), or an out‐group member (Andrews & Rapp, ), presumably because of perceived low credibility. In contrast, participants rely on information more from partners with whom they have a prior relationship (e.g., friends or romantic partners) than from strangers (French, Garry, & Mori, ; Hope, Ost, Gabbert, Healey, & Lenton, ), presumably because of perceived reliability.…”
Section: Social Transmission Of False Memories In Small Groupsmentioning
confidence: 99%
“…For instance, even when we might have read or watched accurate reports of breaking news event, it is possible for us to incorporate related misinformation that a colleague later mentions in conversation. As reviewed earlier, this can happen if we do not actively assess the accuracy of information because of reasons such as perceived or actual expertise, reliability, or confidence of the social source (e.g., Andrews & Rapp, ; Davis & Meade, ; Hope et al., ; Numbers et al., ; Wright et al., ). Future research on conditions that promote the ability to separate fact from fiction is particularly relevant and timely in this Internet age of rapid and vast dissemination of information and misinformation.…”
Section: Social Transmission Of False Memories In Small Groupsmentioning
confidence: 99%
“…For example, socially avoidant participants tend to conform less whereas socially anxious participants tend to conform more (Wright, Busnello, Buratto, & Stein, 2012;Wright, London, & Waechter, 2010). Partner characteristics may also play a role, as participants tend to conform more towards familiar than unfamiliar partners Hope et al, 2008) and more towards younger than older adults (Davis & Meade, 2013;Meade, McNabb, Lindeman, & Smith, 2017).…”
Section: General Audience Summarymentioning
confidence: 99%
“…Post-event discussions are to be expected, as eyewitnesses will often choose to discuss the event with others as a means of validating their own account (Blank, 2009;Williamson, Weber, & Robertson, 2013). However, research has shown that post-event discussions can influence many witnesses into reporting unwitnessed information, learnt from other cowitnesses, into their own statements-a process commonly referred to as memory conformity (Carlucci, Kieckhaefer, Schwartz, Villalba, & Wright, 2010;Davis & Meade, 2013;Garry, French, Kinzett, & Mori, 2008;Paterson & Kemp, 2006b;Paterson, Kemp, & Forgas, 2009;Paterson, Kemp, & McIntyre, 2012;Roediger, Meade, & Bergman, 2001;Wright, Mathews, & Skagerberg, 2005).…”
Section: Introductionmentioning
confidence: 99%